The Implications and Applications of Developmental Spelling After Phonics Instruction - Shane Templeton (Education Sciences)
Examining spelling from a developmental perspective began in the 1970s and has broadened over the years. This research has informed understanding of the nature and development of spelling or orthographic knowledge in children and older students and the role of orthographic knowledge in reading and writing. Based on analyses of the errors that students make in their writing and on spelling assessments, developmental spelling has documented the acquisition and integration of progressively more complex spelling patterns that represent both sound and meaning and illuminated how this information supports students’ ability to read as well as to write words. Intended for researchers, teacher educators, and teachers of students in grades 3–12, this article describes the layers of the spelling system that developmental spelling research has investigated, and their progressive integration in learners, including those who struggle, from the intermediate through the middle and secondary grades. It addresses the implications of developmental spelling research for assessment and instruction in spelling, word analysis, vocabulary, and the more specific implications of developmental spelling research for aligning instruction across spelling, word analysis, vocabulary, morphology, and etymology.